The Influence of Social Media and E-Wom on Revisit Intention at The Lampu Satu Beach Destination in Merauke - Leonora Puspa (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the influence of social media and e-WOM (electronic word of mouth) on revisit intention at Lampu Satu Beach, Merauke. Using a quantitative approach, this study collected data through a survey of beach visitors and analyzed the influence of social media and e-WOM separately and together on revisit intention. The analysis results show that both social media and e-WOM have a positive and significant influence on revisit intention, with both mutually reinforcing each other. Social media, through engaging visual content and interactions with visitors, successfully introduced Lampu Satu Beach, Merauke to a wider audience. On the other hand, e-WOM, consisting of positive reviews and recommendations from previous visitors, increased trust and intention to return. This study also identified that visitors were more likely to repeat their visits after being exposed to positive reviews and engaging content on social media. Based on these findings, it is recommended that the management of Lampu Satu Beach, Merauke, utilize social media and e-WOM in a more integrated manner to increase visitor loyalty and attract new visitors. These strategies may include increasing engagement on social media, encouraging visitors to share their experiences, and maintaining the quality of services and facilities to ensure a satisfying experience for visitors.